Collective Efficacy as a Key Context in Neighborhood Support for Urban Youth. Issue 1 (6th March 2019) - Prince, Dana M.; Hohl, Bernadette; Hunter, Bronwyn A.; Thompson, Azure B.; Matlin, Samantha L.; Hausman, Alice J.; Tebes, Jacob Kraemer
Abstract: Neighborhood context, including the physical and social environment, has been implicated as important contributors to positive youth development. A transactional approach to neighborhood asserts that place and people are mutually constitutive; negative perceptions of place are intrinsically bound with negative portrayals of stigmatized groups, including youth. Adult perceptions of neighborhood youth may contribute to an increased sense of alienation and youth antisocial behavior. This study uses street‐intercept interviews with adults ( N  = 408) to examine the relationship between neighborhood conditions and adult support for neighborhood youth. A path model was used to examine the direct and indirect relationship of neighborhood constructs (safety, aesthetic quality, and walkability) on adult support for neighborhood youth. Neighborhood aesthetic quality and the walking environment were directly associated with adult support for youth, whereas perceived safety was indirectly associated. Collective efficacy partially explained these relationships. Findings support theorized relationships between people and places; improvements to neighborhood physical environment may directly impact resident adults' perceptions of neighborhood young people. Highlights: How adult residents perceive their neighborhood environment impacts neighbors' support for youth. Neighborhood collective efficacy amplifies positive neighborhood support for youth. Place‐based neighborhood initiatives hold promise for impacting residents' support for youth.